Managing Conﬂict To Gets Your Needs Met - Carey, Margaret (Operating Room Nurses Association of Canada Journal, 2000)
When at work, we are all too often met with roadblocks, usually due to some type of disagreement. Whether it is peers with whom our opinions differ, or our inability to express our point, conﬂict occurs. When handling problems, they can become like clouds over the sun, blocking the reality or the sunshine behind the truth. Realistically, we are working towards the same objective - getting the job done.